Glacial-Marine Sedimentation, Canadian Polar Margin, North of Axel Heiberg Island - Hein, Frances; Mudie, Peta (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1991)
ABSTRACTSediment cores, taken at depths of 140 to 300 m across the northwestern shelf of Axel Heiberg Island (82° N), record the deposition of sediments under perennial sea ice. Five sedimentary fades are recognized: (A) soft pebbly-sandy-mud with dropstone structures; (B) bioturbated silty muds; (C) wispy-laminated silty clay/clay; (D) laminated sands/silts and mud; (E) firm pebbly-sandy-mud with chaotic pebble fabrics. Other sediments include terrestrial bedrock of Paleogene Eureka Sound Group, and a younger Tertiary deposit, possibly the Beaufort Formation. Ages range from 1530 ± 60 BP (Fades A) to 9950 ± 80 BP (Fades D). Sedimentation rates vary as follows: - 0.8 cm ka-1, Fades B; 4 cm ka"\ Fades A; 90 cm ka-1, Fades C; 134 cm ka~', Fades D. The sedimentation history, as interpreted from the sedimentology, palynology and foraminiferal results, suggests intervals of more continuous ice cover, with a reduced influx of coarse ice-rafted detritus, alternating with more open water conditions, and high sediment input from meltwater and/or floating icebergs. Only marine sediments overlie Neogene bedrock in the cores. The absence of diamictons at the core sites suggests that grounded ice perhaps never occupied this part of the Axel Heiberg Island shelf. The interpreted history of sedimentation generally corresponds to the land-based record from Ellesmere Island, but differs significantly from marine-based studies in more southern latitudes.